B Cell heterogeneity - difference in the size of B lymphocytes responding to T dependent and T independent antigens. - Gorczynski, R; Feldmann, M (1975)
Spleen cells from either normal (nonimmunized) mice or mice preimmunized with TNP KLH were depleted of T cells by treatment with a heterologous anti θ serum and complement. Fractionation of these B cells by velocity sedimentation followed by challenge with either a T independent antigen (DNP POL) or a T dependent antigen (TNP KLH), the latter being performed in the presence of additional helper T cells, revealed apparent size difference between B cells responding to the two antigens. This difference, while most marked with preimmunized B cells, was also apparent with normal B cells from the spleen or bone marrow, but not from the lymph node. Similar data were observed with other T dependent and T independent antigens. The differences in the sedimentation profile of splenic B cells for T dependent and T independent antigens did not seem to be due to a difference in the kinetics of appearance of antibody upon stimulation with these antigens, though large B cells did seem to give rise to antibody producing cells at later times than small B cells. © 1975.